2005
DOI: 10.1177/1099800404271916
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Changes in Cerebral Spinal Fluid Phosphatidylcholine during Treatment for Acute Lymphoblastic Leukemia

Abstract: Central nervous system (CNS) treatment contributes to improved long-term disease-free survival from childhood acute lymphoblastic leukemia (ALL) by significantly decreasing the rate of disease relapse. Methotrexate (MTX), a drug commonly used for CNS treatment, has been associated with cognitive and academic problems, white-matter changes, perfusion defects, and brain atrophy. This study investigated oxidative stress as a possible mechanism of chemotherapy induced CNS injury. Unoxidized and oxidized components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 36 publications
4
42
0
1
Order By: Relevance
“…Therefore, PC and PI can be simultaneously monitored at these two wavelengths. 54, 56 Chromatograms showing separation of the components of PI (elution time approximately 14 minutes) and PC (elution time approximately 31.5 minutes) are illustrated in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, PC and PI can be simultaneously monitored at these two wavelengths. 54, 56 Chromatograms showing separation of the components of PI (elution time approximately 14 minutes) and PC (elution time approximately 31.5 minutes) are illustrated in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…It is likely that the increased levels of lipid peroxides in the spinal CSF may cause lipid peroxidation. Some disease [24][25][26] and some drugs used to treat illness 13,27 causes alteration on the free radical defence mechanisms and lipid peroxidation products in CSF. So, it is suggested that the oxidation of CSF lipoproteins play a role in the pathogenesis of neurodegenerative diseases.…”
Section: Disscussionmentioning
confidence: 99%
“…Furthermore, to measure biochemical parameters in the serum and urine that may be correlated with the MTX effects in tissues. 13 At last, we intend to assess to what extend GSE, a potent free radical scavenger, could ameliorate the acute MTX-induced effects in young specimens investigated.…”
Section: Introductionmentioning
confidence: 99%